2011
DOI: 10.1002/dvdy.22694
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative three‐dimensional imaging of live avian embryonic morphogenesis via micro‐computed tomography

Abstract: Many clinically relevant congenital malformations arise during mid to late embryonic stages. This period is challenging to image quantitatively in live embryos, necessitating the use of multiple specimens with increased experimental variability. Here we establish X-ray and blood-pool computed tomography (CT) contrast agent toxicity and teratogenesis thresholds for 3D Micro-CT imaging of live avian embryos. Day 4 chick embryos micro-injected with Visipaque™ (VP) developed for an additional 6 days without defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…The same challenges were addressed by some other investigators, highlighting the recent attention placed on the development of a non-destructive high-resolution scanning method and its importance. For example, Henning et al 17 developed a technique for injecting non-toxic contrast agents through the vitelline vessels and for subsequent high resolution micro-CT imaging of the chick embryo. The authors found that their technique could similarly be used repeatedly on the same chick embryo without harming it, thus enabling longitudinal studies like our technique.…”
Section: Discussionmentioning
confidence: 99%
“…The same challenges were addressed by some other investigators, highlighting the recent attention placed on the development of a non-destructive high-resolution scanning method and its importance. For example, Henning et al 17 developed a technique for injecting non-toxic contrast agents through the vitelline vessels and for subsequent high resolution micro-CT imaging of the chick embryo. The authors found that their technique could similarly be used repeatedly on the same chick embryo without harming it, thus enabling longitudinal studies like our technique.…”
Section: Discussionmentioning
confidence: 99%
“…Omnipaque is administered to a live specimen but it is lethal within 24 hours making it ineffective for longitudinal studies (Henning, Jiang et al 2011)…”
Section: 0 Materialsmentioning
confidence: 99%
“…Visipaque is administered to a live specimen and has shown to be nonembryotoxic (Henning, Jiang et al 2011)…”
Section: 0 Materialsmentioning
confidence: 99%
See 2 more Smart Citations